PENERAPAN PENDEKATAN CONFERENCING UNTUK MENINGKATKAN KETERAMPILAN DISKUSI SISWA KELAS VI SD NEGERI 060857 MEDAN TEMBUNG - Harahap, Zakiah Marito; Zakiah Marito Harahap; Lydia Roida Sihombing (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the discussion skills of students before applying the Conferencing approach in science lessons for sixth-grade students at State Elementary School 060857 Medan Tembung, to assess the discussion skills of students after applying the Conferencing approach in science lessons for sixth-grade students at State Elementary School 060857 Medan Tembung, and to evaluate the improvement in students' discussion skills on science material after implementing the Conferencing approach in sixth grade at State Elementary School 060857 Medan Tembung. This research uses a quantitative approach. The results of the research based on the observations conducted show that during the pre-test, 13 students were not yet proficient, accounting for 48.1%, while 14 students were deemed proficient, making up 51.9%. The students' discussion skills using the conferencing approach in Cycle I did not meet the Minimum Competency Criteria (KKM), with only 3 students meeting the KKM, while 24 students did not. In Cycle II, the students' discussion skills using the conferencing approach met the KKM standards, with 26 students meeting the KKM and 1 student not meeting the KKM. The gain calculation yielded an average of 64.96 for Cycle I and an average of 84 for Cycle II, resulting in a gain of 54.4%. This indicates that VI State Elementary School 060857 Medan Tembung experienced a moderate improvement in discussion skills, as it falls within the 31-70% category.